Evaluation of Litchi Based Agri-horticultural System on Degraded Land in Doon Valley - Lal, H.; Samra, J. S.; Tiwari, R.K.; Tomar, D.S. (Indian Journal of Agroforestry, 2020)
The results of one field experiment conducted for five years (1997-2001) showed that litchi (Litchi chinensis-cv. Rose scented) plantation based agri-horticultural system can be raised on degraded gravelly riverbed land in Doon Valley having cowpea, okra, sesame, blackgram and pigeonpea, as inter crops during kharif season and toria during rabi season. On an average duringÂ Kharif season, cowpea and okra produced 20.24 and 29.16 q ha-1 pods and sesame, black gram and pigeon pea 2.41, 5.27 and 3.80 q ha-1 grains, respectively. However, toria grown in sequence with cowpea, okra, sesame and black gram produced 5.00, 3.85, 4.26 and 5.19 q ha-1 grains and 18.75, 21.92, 16.70 and 19.25 q ha-1 stover yield, respectively during rabi season. The highest net profit of Rs.4554 ha-1 was obtained from okra-toria cropping system followed by cowpea-toria (Rs. 1270 ha-1) and black gram-toria (Rs. 779 ha-1) cropping systems with benefit cost ratio of 1.27, 1.08 and 1.05, respectively. Pigeon pea supplemented 23.15, 8.90, 49.96, 58.70 and 42.95 kg ha-1 nitrogen, phosphorus, potassium, calcium and magnesium, respectively per year through residue followed by okra, cowpea, black gram, toria and sesame. Cowpea-toria and black gramtoria cropping systems improved Nand P contents of litchi leaf. The plant growth characters of litchi did not influence by any inter crops.